MANAJEMEN RETRIBUSI PELAYANAN PERSAMPAHAN DI KABUPATEN MAMUJU - Andriani Andriani (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2017)
This study aims to find out how management is applied in waste service fees in Mamuju District, which was carried out by the Regional Environmental Agency of Mamuju Regency. This type of research is descriptive qualitative which provides an overview or explanation of the management of solid waste services in the sub-district of Mamuju, as well as the obstacles. The results of the study showed that Mamuju regency waste collection planning consisted of setting targets, collecting data on retribution and socialization. Planning runs less effectively. In terms of data collection, the Environmental Agency does not directly go down the field to carry out data collection, only based on data from PLN and PDAM. Then in terms of socialization it has not been evenly distributed to the community so that many people do not yet know about the existence of local regulations on waste retribution.